2010
DOI: 10.1521/aeap.2010.22.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Men Who Have Sex With Men for Large HIV Intervention Trials: Analysis of the EXPLORE Study Recruitment Effort

Abstract: Testing HIV prevention strategies requires that researchers recruit participants at high risk of HIV infection. Data from the EXPLORE Study, a behavioral intervention trial involving men who have sex with men, were used to examine the relationship between recruitment strategies and participant characteristics, sexual risk behaviors and HIV incidence. The EXPLORE Study used a wide variety of recruitment strategies; no one strategy accounted for more than 20% of enrolled men. Younger men and men of color were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
(26 reference statements)
1
12
0
Order By: Relevance
“…Field-based recruitment reached a greater proportion of men who identified as HIV-negative compared to men in our Internet-based sample, which is consistent with prior findings 56 , but contradicts those reported elsewhere more recently (see Barresi et al 49 , who found higher rates of seropositivity in field- compared to Internet-based samples). Relatedly, our Internet-based sample overall endorsed higher levels of sexual risk behavior (e.g., unprotected sex,) in accordance to previous studies (for example, Evans et al 37 conducted a study in Great Britain and found that MSM recruited over the Internet were more likely to report unprotected anal sex.)…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Field-based recruitment reached a greater proportion of men who identified as HIV-negative compared to men in our Internet-based sample, which is consistent with prior findings 56 , but contradicts those reported elsewhere more recently (see Barresi et al 49 , who found higher rates of seropositivity in field- compared to Internet-based samples). Relatedly, our Internet-based sample overall endorsed higher levels of sexual risk behavior (e.g., unprotected sex,) in accordance to previous studies (for example, Evans et al 37 conducted a study in Great Britain and found that MSM recruited over the Internet were more likely to report unprotected anal sex.)…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, though, once MSM were enrolled and attended the intervention, retention for follow-up assessments did not differ by recruitment method. Although the EXPLORE intervention trial did not utilize Internet-based recruitment efforts, field-based recruitment efforts were more effective at reaching younger MSM, MSM of color, and HIV-positive MSM than were print ads and other methods of recruitment 49 . The EXPLORE study also found that, although there were no differences in HIV incidence by recruitment strategy, MSM reporting 10 or more sexual partners were more likely to be recruited via field-based efforts, and MSM reporting unprotected anal sex were more likely to be recruited via clinic-based efforts.…”
mentioning
confidence: 99%
“…Men were excluded if they reported that they had been involved in a mutually monogamous relationship for 2 or more years with a male partner known to be negative for HIV antibodies. The recruitment, sampling, data collection, measures, and other methods of the EXPLORE Study have been described in detail elsewhere (Barresi et al, 2010; Chesney et al, 2003; Koblin et al, 2003; Koblin, Chesney, & Coates, 2004). In brief, participants were recruited using street- and venue-based outreach in areas where MSM were known to congregate (e.g., dance clubs, bathhouses, health clubs).…”
Section: Methodsmentioning
confidence: 99%
“…Because different recruitment strategies vary in the characteristics of the samples they yield (Fisher, Purcell, Hoff, Parsons, & O’Leary, 2006; Grov, 2012; Parsons et al, 2013; Vial, Starks, & Parsons, 2014), knowing where to concentrate efforts can maximize the likelihood of reaching specific subgroups of HIV-positive MSM. However, despite the potential utility of this information, few studies report associations among recruitment venue and risk behaviors or HIV prevalence (Barresi et al, 2010). …”
mentioning
confidence: 99%